In vitro effects of docosahexaenoic and eicosapentaenoic acid on human meibomian gland epithelial cells. (November 2015) - Hampel, Ulrike; Krüger, Magret; Kunnen, Carolina; Garreis, Fabian; Willcox, Mark; Paulsen, Friedrich
Abstract: To investigate the effect of ω-3 fatty acids on human meibomian gland epithelial cells (HMGECs, cell line) in vitro . HMGECs were stimulated with docosahexaenoic acid (DHA) or combinations with eicosapentaenoic acid (EPA) and acetyl sialic acid (ASA). Sudan III fat staining, viability and proliferation assays, electric cell-substrate impedance sensing, real-time PCR for gene expression of cyclooxygenase-2 and 15-lipoxygenase and ELISAs for resolvin D1 (RvD1), IFNγ, TNFα and IL-6 were applied. Lipid droplet accumulation and viability was increased by 100 μM DHA in the presence or absence of EPA in serum cultured HMGECs. In contrast, HMGECs cultured with DHA and EPA under serum-free conditions showed minimal lipid accumulation, decreased proliferation and viability. Normalized impedance was significantly reduced in serum-free cultured HMGECs when stimulated with DHA and EPA. HMGECs cultured in serum containing medium showed increased normalized impedance under DHA and EPA stimulation compared to DHA or EPA alone or controls. IL-6 and IFNγ were downregulated in HMGECs treated for 72 h with DHA and EPA. In general, TNFα, IFNγ and IL-6 levels were decreased after 72 h compared to 24 h in serum containing medium with or without DHA or EPA. The concentration of RvD1 was elevated 2-fold after DHA treatment. Cyclooxygenase-2 gene expression decreased compared to controls during DHA stimulation after 72 h. Treatment with DHA and ASA revealed a decreased 15-lipoxygenase gene expression which was reduced after three days of DHA incubation. DHA and EPA supplementation affected HMGECs in vitro and supported anti-inflammatory effects by influencing cytokine levels, decreasing COX-2 expression and increasing the production of RvD1. Highlights: Human meibomian gland epithelial cells (HMGEC, cell line) can accumulate docosahexaenoic acid (DHA). HMGEC show increased normalized impedance under DHA and EPA stimulation compared to DHA or EPA alone or controls. The cytokines IL-6 and IFNγ are downregulated in HMGEC upon DHA stimulation. DHA stimulation increases Resolvin D1 production in HMGEC. Cyclooxygenase-2 and 15-lipoxygenase gene expression is decreased in HMGEC under DHA stimulation.